2014
DOI: 10.1002/anie.201406258
|View full text |Cite
|
Sign up to set email alerts
|

An Organotrifluoroborate for Broadly Applicable One‐Step 18F‐Labeling

Abstract: A new zwitterionic organotrifluoroborate is appended to three radiosynthons that afford undergo facile bioconjugation to several clinically relevant peptides and one enzyme inhibitor. Molecularly complex bioconjugates are (18)F-labeled in a single aqueous step in rapid time (<15 min) without HPLC purification to afford tracers in good yields (>200 mCi, 20-40%) at high specific activity (≥3 Ci/μmol) and at >98% purity. PET imaging shows in vivo stability and tumor uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 35 publications
1
129
0
3
Order By: Relevance
“…29 In this study, we introduced a novel GRPR-targeting peptide 18 FAmBF 3 -MJ9 for PET imaging of prostate cancer. AmBF 3 -MJ9 was designed for labeling via the 18 F-19 F isotope exchange reaction on AmBF 3 recently reported by Perrin et al 23,31 The AmBF 3 -conjugated alkyne 2 was coupled to an RM26 derivative, azidoacetyl-MJ9, via Cu-catalyzed 2+3 dipolar cycloaddition to yield AmBF 3 -MJ9. The affinity of the parent peptide (H-D-Phe-Gln-Trp-Ala-Val-Gly-His-(3S,4S)AHMHA-Leu-NH 2 ) was measured in rat pancreatic acini by Llinares et al, and found to be 0.9 nM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 In this study, we introduced a novel GRPR-targeting peptide 18 FAmBF 3 -MJ9 for PET imaging of prostate cancer. AmBF 3 -MJ9 was designed for labeling via the 18 F-19 F isotope exchange reaction on AmBF 3 recently reported by Perrin et al 23,31 The AmBF 3 -conjugated alkyne 2 was coupled to an RM26 derivative, azidoacetyl-MJ9, via Cu-catalyzed 2+3 dipolar cycloaddition to yield AmBF 3 -MJ9. The affinity of the parent peptide (H-D-Phe-Gln-Trp-Ala-Val-Gly-His-(3S,4S)AHMHA-Leu-NH 2 ) was measured in rat pancreatic acini by Llinares et al, and found to be 0.9 nM.…”
Section: Discussionmentioning
confidence: 99%
“…23 All other chemicals and solvents were obtained from commercial sources, and used without further purification. [ 125 I-Tyr 4 ]-Bombesin (81.4 TBq/mmol) was purchased from Perkin Elmer (Waltham, MA).…”
Section: Chemicals and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…These laborious procedures, such as azeotropic drying and HPLC purification, often reduce the radiochemical yield, while at the same time they increase the risk of synthetic failure. To solve these problems, a one-step and easy-to-follow protocol is described here for peptide radiolabeling that is based on the use of a recently developed organotrifluoroborate 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on in vitro assays, the uptake of 18 F-BAA is mediated by various amino acid transporters and they are kinetically indistinguishable from natural amino acids, and hence they truly mirror the uptake behavior of natural amino acids, although they are not incorporated into proteins. With this strategy of amino acid mimicry, in addition to t h e o n e -s t e p 1 8 F -l a b e l i n g m e t h o d u t i l i z i n g a n organotrifluoroborate which was also developed by the same investigators [16,17], the BAAs may serve as general PET imaging probes for amino acid transporters. All amino acids can be radiolabeled in a similar fashion for imaging amino acid transporter activity and tumor metabolism, which could complement the use of 18 F-FDG in the imaging of tumor types in which 18 F-FDG does not work well (e.g.…”
mentioning
confidence: 99%